Factors Influencing Infection Rates after Open Hand Fractures - Reasoner, Kaitlyn; Desai, Mihir J.; Lee, Donald H. (Journal of Hand and Microsurgery, 2019)
Introduction Open hand fractures are anecdotally reported to have lower infection rates than open long bone fractures. Although a 3-hour rule for antibiotic administration and a 6-hour rule for operative debridement have historically been upheld as ideal management for open fractures, other factors may be more influential in the development of infection. The purpose of this study was to investigate factors associated with open hand fracture infections.Materials and Methods We retrospectively reviewed 67 patients with 107 open hand fractures between 2012 and 2017. Time from injury to antibiotic administration and operative debridement, modified Gustilo–Anderson classification, and patient characteristics including age, smoking status, and presence of chronic disease were examined for each patient. Outcome parameters were the development of infection and fracture union.Results The overall rate of infection was 9% (6 of 67 patients). No type 1 or type 2 fractures developed infection in contrast to 12.2% of type 3 fractures. Patients who received antibiotics in less than 3 hours and underwent debridement in less than 6 hours did not have lower infection or nonunion rates than those who did not. The association between the modified Gustilo–Anderson classification and the development of infection or nonunion was statistically significant.Conclusion Factors including time to antibiotics, time to operative debridement, smoking status, and chronic disease comorbidities were not predictive of either infection or nonunion in open hand fractures. Fracture type as defined by a modified Gustilo–Anderson classification was the factor most strongly related to the development of infection or nonunion in these fractures.
Keywords: open fractures; hand fractures; trauma; infection; non-union